Minimally invasive (MIE) vs open surgery for cancer of esophagus and GE junction. Long term results - Thakur, Binay; Yonghui, Di; Devkota, Mukti; Baral, Paribartan; Regmi, Yogesh; Malli, Rajendra; Tiwari, Upsana (Journal of Society of Surgeons of Nepal, 2016)
Introduction: MIE is becoming a preferred approach for cancer of esophagus and GE junction, but its benefits have yet to be confirmed in randomized controlled trials. We performed a retrospective comparison between these two approaches for complications and survival results. Methods: Patients primarily going for surgery or after neoadjuvant chemo/ chemoradiation were reviewed. MIE varied from totally thoracoscopic and laparoscopic to a hybrid approach. Both MIE and Open approaches were a three, two or one incision procedures. Results: MIE and open surgery were done in 128 and 293 patients, respectively. The mean basic parameters (referred as MIE/ Open) – age (59/ 57 years), duration of dysphagia (4/ 4 months), weight loss (8/ 9 kg), postoperative stay (13/ 14 days), hospital mortality (3/ 17), anastomotic leak (17/ 32), hoarseness of voice (8/ 16), number of harvested nodes (21/ 22), and R0 resection (122/ 263) did not differ significantly (p = ns). Mean operative time (265/ 240 mins) and intraoperative blood loss (325/ 436 ml) differed significantly (p < 0.05). Postoperative pneumonia was significantly less in MIE group (p<0.001). Median and 5-year overall survival was 33 months and 21% in MIE group; and 27 months and 20% in open group (p = 0.2) Conclusion: MIE and Open surgery did not differ in major postoperative complications except postoperative pneumonia, which was less in MIE. Both the procedures were similar in achieving R0 resection, median and 5-year overall survival.